Earning American college credit in China: New model for transfer college credit program - Hu, Jiayi; Hagedorn, Linda Serra (Journal of Interdisciplinary Studies in Education, 2013)
The concept of Transfer College Credit Programs (TCCP) has spread to the far corners of the Earth. There are two types of TCCPs: 1) high school students around the globe planning on attending American colleges or universities enroll in college-level courses while still in high school in their home country and earn American college credits which are later transferred to their American institutions, and 2) currently enrolled international undergraduate students taking courses offered during summer break in their home countries and transferring the credits back to their university. This study investigates the popularity of these programs in China, and illustrates a typology of TCCPs offered in China.